Marij Pregelj: slikarstvo skrajnosti - Zgonik, Nadja (Zbornik za umetnostno zgodovino (Nova vrsta), 1988)
The paper discusses the complex creative activity of the Slovene painter Marij Pregelj. Pregelj's very autobiographical painting was always a response to the reality which surrounded him and determined his life. His central motif was human figure which changed with time from specific, still recognizable, forms to expressively deformed metaphors of universal human suffering.